Obama and the Biracial Factor : The Battle for a New American Majority - Jolivette, Andrew; Jolivette, Andrew (Book collections on Project MUSE., 2012)
Obama and the Biracial Factor is the first book to explore the significance of mixed-race identity as a key factor in the election of President Obama and examines the sociological and political relationship between race, power, and public policy in the United States.